The Relationship Between Mental Workload and Work Stress in Nurses at the Inpatient Installation - Shaifuddin, Zakky; Chairani, Aulia; Hardieni, Niniek; Kristanti, Melly (Public Health Undergraduate Program, Faculty of Health Science, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Nurses in inpatient settings face huge responsibilities, both physical and mental, such as looking after patients, providing emotional support, and handling high work demands. Excessive mental workload can trigger job stress, reduce productivity, and lower the quality of health services. This study explored the relationship between mental workload and job stress in nurses in inpatient settings. Method: This study was an analytical quantitative research with a cross-sectional design. It was conducted from January to June 2023. The research instruments were the NASA-TLX questionnaire for mental workload and the job stress scale. The population consisted of 133 nurses, with a sample of 75 people selected by consecutive sampling. The independent variable was mental workload, while the dependent variable was job stress. Data analysis used the Chi-Square test with p<0.05 as significant. Result: Sixty-four percent of nurses experienced a moderate mental workload, and 36% experienced a heavy workload. A total of 53.3% of nurses reported experiencing work stress. The analysis showed a significant relationship between mental workload and work stress (p=0.034), where work stress was more common among nurses with a moderate to severe mental workload. Conclusion: There was a significant relationship between mental workload and work stress in nurses. To reduce mental workload and work stress, it is recommended that work management be improved, such as by redistributing tasks and providing psychological support. Stress management training and effective communication should also improve nurses' well-being.